Process for preparation of zirconia blanks

A novel zirconia blank production process using a specific suspension and rapid firing technique addresses the inefficiencies of conventional methods, enabling rapid production of high-quality dental restorations with enhanced optical properties.

JP7599274B2Active Publication Date: 2024-12-13IVOCLAR VIVADENT AG
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2019213918
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-11-29
Filing Date
2019-11-27
Publication Date
2024-12-13
Estimated Expiration
2039-11-27

AI Technical Summary

Technical Problem

Conventional processes for producing zirconia blanks are labor-intensive and time-consuming, requiring over 4 hours for dense firing, which hinders the rapid production of dental restorations with desired optical properties.

Method used

A process involving a zirconia suspension with specific particle size and composition is introduced into a porous mold, followed by medium removal and mold demolding, allowing for rapid densification firing within 120 minutes to produce blanks with high translucency and mechanical properties.

Benefits of technology

The process enables the production of dental restorations with excellent optical and mechanical properties in a significantly shorter time, facilitating 'patient chairside' procedures by reducing processing time to under 2 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599274000001
    Figure 0007599274000001
  • Figure 0007599274000002
    Figure 0007599274000002
Patent Text Reader

Abstract

To provide a process for preparation of a zirconia blank.SOLUTION: In a process for preparation of a zirconia blank, (a) a suspension of zirconia in a liquid medium is introduced into a mold having pores, (b) the liquid medium is at least partially removed via the pores, and (c) the blank formed is removed from the mold, where the suspension has a zirconia content of 68-88 wt.%, particularly 70-86 wt.%, and preferably 75-85 wt.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a process for the preparation of zirconia blanks which, after desired shaping, can be densely fired within a very short time to form dental restorations with outstanding optical properties. [Background technology]

[0002] Zirconia ceramics are often used for the manufacture of fully anatomical dental restorations. They offer high clinical safety, are metal-free, can be used in minimally invasive preparations, and are very attractively priced compared to other metal-free restorations. These restorations are usually milled or ground from pre-fired blanks, dense-fired by heat treatment, and finally, veneered and / or polished as required.

[0003] Processes for the preparation of zirconia blanks and their machining to form dental restorations are known.

[0004] WO 2014 / 209626 describes a process for producing zirconia blanks that, after pre-firing and machining by a CAD / CAM process, can be densely fired at temperatures below 1200°C to form dental restorations. These restorations are characterized by being not only translucent but also opalescent. To produce these blanks, a nanoscale zirconia particle suspension having an average primary particle size of 20 nm or less is poured into a corresponding mold, for example. However, the preparation of this suspension is laborious because commercially available suspensions used as raw materials first require a lengthy concentration step. The green compact obtained by casting also needs to be dried very slowly to avoid crack formation, which can take several days, especially for thicker blanks. Finally, the dense firing procedure is also very time-consuming, taking more than four hours, which hinders the patient's desire for a rapid completion of the restoration that is ground and milled from the blank.

[0005] WO 2009 / 061410 and WO 2013 / 181018 describe processes for preparing zirconia blanks by slip casting of a suspension. These blanks are said to produce translucent dental restorations after drying, pre-firing, machining, e.g., by a CAD / CAM process, and subsequent dense firing. However, no specific examples of the process and suspension used are given, nor are the exact conditions for dense firing, and in particular its duration, specified.

[0006] EP 826 642 describes a process for producing ceramic frameworks for dental restorations, which involves slip-casting a suspension containing alumina and zirconia particles to form a ceramic film, layering the film onto a dental plaster model, applying pressure to bond the film to the model, heat-treating at 500°C, firing at 1150°C, coating the fired body with glass powder, and further heating.

[0007] Korean Patent No. 101416654 describes a process for the production of ZrO2 blocks using zirconia waste (e.g., that accumulated in dental laboratories, among others). From this waste, after debinding and grinding, an aqueous zirconia suspension is produced, from which solids of the desired shape are produced by slip casting. These solids are cold isostatically pressed and then fired twice.

[0008] WO 2018 / 049331 describes dental zirconia blanks for CAD / CAM applications that exhibit a gradient of properties, and in particular a gradient of color, due to the use of different ZrO particles. These blanks can be formed by slip casting a mixture of suspensions containing zirconia particles of different shades and sizes, where the different settling behavior of these particles is to be exploited.

[0009] However, conventional processes for the production of zirconia blanks are laborious, and the blanks produced therefrom require long processing times for dense firing, particularly to achieve the desired optical properties (e.g., high translucency). The entire process of dense firing a conventional blank (starting with heating to firing temperature and ending with cooling to room temperature) typically takes significantly longer than 4 hours, which contributes significantly to the unsatisfactory long duration for processing to form dental restorations. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] International Publication No. 2014 / 209626 [Patent Document 2] International Publication No. 2009 / 061410 [Patent Document 3] International Publication No. 2013 / 181018 [Patent Document 4] European Patent Application Publication No. 826 642 [Patent Document 5] Korean Patent No. 101416654 [Patent Document 6] International Publication No. 2018 / 049331 Summary of the Invention [Means for solving the problem]

[0011] It is therefore an object of the present invention to provide a process for the preparation of zirconia blanks which avoids the drawbacks of conventional processes and makes it possible to produce, in a short time, blanks which can be processed to form dental restorations having very good optical and mechanical properties.

[0012] This object is achieved according to the invention by processes for preparing zirconia blanks according to claims 1 to 16. The subject of the invention is also zirconia blanks according to claims 17 to 19, the use of zirconia blanks according to claim 20, and processes for preparing dental restorations according to claims 21 to 24.

[0013] The present invention provides, for example: (Item 1) 1. A process for the preparation of a zirconia blank, comprising: (a) A suspension of zirconia in a liquid medium is introduced into a mold having a porous structure; (b) the liquid medium is at least partially removed through the pores; and (c) the formed blank is removed from the mold; A process wherein the suspension has a zirconia content of 68 to 88% by weight, in particular 70 to 86% by weight, and preferably 75 to 85% by weight. (Item 2) The zirconia in the suspension has a particle volume of d 50 The process according to the preceding item, wherein the particle size, measured as a ρ value, is 50 to 250 nm, in particular 60 to 250 nm, and preferably 80 to 250 nm. (Item 3) Item 10. The process of any of the preceding items, wherein the zirconia in the suspension has a primary particle size of 30 to 100 nm. (Item 4) The process according to any of the preceding items, wherein the zirconia is stabilized with Y2O3, La2O3, CeO2, MgO and / or CaO, and in particular with 2 to 14 mol%, preferably 2 to 10 mol%, and particularly preferably 2 to 8 mol% of these oxides relative to the zirconia content. (Item 5) Item 10. The process of any of the preceding items, wherein the liquid medium contains water. (Item 6) The process according to any of the preceding items, wherein the liquid medium contains organic components in an amount of not more than 5% by weight, in particular not more than 3% by weight, preferably not more than 2% by weight and particularly preferably not more than 1% by weight, relative to the amount of solids in the suspension, or in an amount of 0.05 to 5% by weight, in particular 0.1 to 3% by weight, preferably 0.1 to 2% by weight and particularly preferably 0.1 to 1% by weight, relative to the amount of solids in the suspension. (Item 7) The process according to any of the preceding items, wherein the liquid medium contains at least one compound selected from amino alcohols, glycols, carboxylic acids and carboxylates, preferably at least one compound selected from ethanolamine, ethylene glycol, dipropylene glycol, citric acid and citrates. (Item 8) The suspension is heated for 0.1 to 1000 s -1 The process according to any of the preceding items, wherein the viscosity of the emulsion is 5 to 500 mPas, in particular 5 to 400 mPas, and preferably 5 to 300 mPas, measured at a shear rate of 100 rpm and a temperature of 25°C. (Item 9) 10. The process according to any of the preceding items, wherein the suspension contains a mixture of zirconia powders having different compositions, in particular a mixture of zirconia powders having different colors and / or translucencies. (Item 10) Item 10. The process according to any of the preceding items, wherein in step (a), suspensions of zirconia powders having different compositions, in particular suspensions of zirconia powders having different colors and / or translucencies, are introduced into the mold one by one in sequence. (Item 11) Item 10. The process according to any of the preceding items, wherein the blank is a block, a block with an interface, a disc, or a tooth-like preform. (Item 12) 10. The process according to any of the preceding items, wherein the blank formed in step (c) has a holding device, in particular formed integrally with the blank. (Item 13) The process according to any of the preceding items, wherein the blank formed in step (c) is dried, in particular at a temperature of 20 to 60°C, preferably 20 to 50°C, and particularly preferably 20 to 40°C. (Item 14) The blank has a viscosity of 3.3 to 4.0 g / cm 3 , especially 3.35 to 3.9 g / cm 3 , and preferably 3.4 to 3.9 g / cm 3 density of, and / or 0.08~0.14cm 3 / g, especially 0.08~0.12cm 3 / g, and preferably 0.08 to 0.10 cm 3 / g pore volume, and / or D relative to particle volume 50 pore diameters, measured as values, of 0.02 to 0.12 μm, in particular 0.03 to 0.10 μm, and preferably 0.04 to 0.08 μm Item 1. The process of any of the preceding items, comprising: (Item 15) The process according to any of the preceding items, wherein the blank is pre-fired, in particular at a temperature in the range of 600 to 1100°C, preferably 700 to 1050°C, and particularly preferably 800 to 1000°C. (Item 16) The pre-fired blank is 3.4~4.0g / cm 3 , especially 3.5 to 4.0 g / cm 3 , and preferably 3.6 to 3.9 g / cm 3 density of, and / or 0.08~0.14cm 3 / g, especially 0.08~0.12cm 3 / g, and preferably 0.09 to 0.11 cm 3 / g pore volume, and / or a maximum pore diameter of less than 0.15 μm, in particular less than 0.12 μm, and preferably less than 0.08 μm Item 1. The process of any of the preceding items, comprising: (Item 17) A zirconia blank obtainable by the process described in any of the preceding items. (Item 18) A pre-fired zirconia blank, comprising: 3.4~4.0g / cm 3 , especially 3.5 to 4.0 g / cm 3 , and preferably 3.6 to 3.9 g / cm 3 density of, and / or 0.08~0.14cm 3 / g, especially 0.08~0.12cm 3 / g, and preferably 0.09 to 0.11 cm 3 / g pore volume, and / or a maximum pore diameter of less than 0.15 μm, in particular less than 0.12 μm, and preferably less than 0.08 μm A zirconia blank having (Item 19) 2. A zirconia blank according to any of the preceding items, having a linear shrinkage of less than 18%, in particular less than 17%, and preferably less than 16%. (Item 20) 10. Use of a blank according to any of the preceding items for the preparation of a dental restoration. (Item 21) 1. A process for the preparation of a dental restoration, in which a blank according to any of the preceding items is given the shape of the dental restoration and the blank is dense-sintered at a firing temperature of 1200 to 1600°C, in particular 1300 to 1550°C, and preferably 1350 to 1500°C. (Item 22) 10. The process according to claim 1, wherein the period for heating the blank from room temperature to the firing temperature, holding at the firing temperature and cooling to the final temperature is 120 minutes or less, in particular 60 minutes or less, preferably 40 minutes or less, and particularly preferably 30 minutes or less. (Item 23) The blank is (a) subjected to a first heat treatment; (b) subjected to a second heat treatment; and (c) cooled; The process of any of the preceding items, wherein the heat treatment in step (a) is carried out at a lower pressure than the heat treatment in step (b). (Item 24) The process according to any of the preceding items, wherein the dental restoration is a bridge, inlay, onlay, crown, implant, veneer, occlusal surface or abutment.

[0014] Abstract The present invention relates to a process for the preparation of zirconia blanks by introducing a zirconia suspension into a porous mold and ejecting the formed blank from the mold, and to the use of the formed, optionally pre-fired, blank for the preparation of dental restorations using a very short dense firing process. DETAILED DESCRIPTION OF THE INVENTION

[0015] The process for the preparation of zirconia blanks according to the present invention comprises: (a) a suspension of zirconia in a liquid medium is introduced into a mold having fine pores; (b) the liquid medium is at least partially removed through these pores; and (c) The formed blank is removed from this mold. wherein the suspension has a zirconia content of 68 to 88% by weight, preferably 70 to 86% by weight, and particularly preferably 75 to 85% by weight.

[0016] Surprisingly, it has been found that after corresponding shaping, the blanks obtainable by the process according to the present invention can be densely fired to form dental restorations in only a very short time, and yet these dental restorations have very good optical properties, and in particular, high translucency, and therefore meet even the highest aesthetic demands for dental restorations. Thus, it is possible for a patient to produce a dental restoration from the desired shaped and densely fired blank and fit it to the patient after just one appointment with the dentist. Such rapid provision of a dental restoration, also referred to as a "chairside" procedure, is naturally very attractive to patients. Therefore, the process according to the present invention is significantly superior to conventional processes, in which very long firing times must be tolerated just to achieve satisfactory translucency.

[0017] The zirconia in suspension is d relative to the particle volume. 50 The particle size, measured as a function of the particle size, is in particular 50 to 250 nm, preferably 60 to 250 nm, and in particular 80 to 250 nm, determined in particular by the static laser scattering (SLS) process in accordance with ISO 13320:2009, for example using an LA-960 particle analyzer (Horiba), or by the dynamic light scattering (DLS) process in accordance with ISO 22412:2017, for example using a NANO-flex particle measuring device (Colloid Metrix).

[0018] The primary particle size of zirconia is typically in the range of 30 to 100 nm and is usually also determined using the dynamic light scattering (DLS) process as described above or by scanning electron microscopy.

[0019] The zirconia is, in particular, zirconia based on tetragonal zirconia polycrystal (TZP). Preferred is zirconia stabilized with Y2O3, La2O3, CeO2, MgO and / or CaO, in particular zirconia stabilized with 2 to 14 mol%, preferably 2 to 10 mol%, and particularly preferably 2 to 8 mol% of these oxides, based on the zirconia content.

[0020] The zirconia used in the process according to the invention can also be colored. The desired color is achieved, in particular, by adding one or more coloring elements to the zirconia. The addition of coloring elements, sometimes referred to as doping, is usually carried out during the preparation of the zirconia powder by coprecipitation and subsequent calcination. Examples of suitable coloring elements are Fe, Mn, Cr, Ni, Co, Pr, Ce, Eu, Gd, Nd, Yb, Tb, Er, and Bi.

[0021] The zirconia in the suspension may also be a mixture of zirconia powders with different compositions, which may in particular result in different colors and / or translucencies in the final dental restoration. Thus, with the aid of a mixture of zirconia powders of different colors, the desired color for the dental restoration produced from this blank can be easily and specifically set. In the same way, the translucency of the dental restoration produced can also be specifically adjusted by using a mixture of zirconia powders with different translucencies. The degree of translucency of the dental restoration produced can be controlled, in particular, by the yttrium oxide content of the zirconia powder used.

[0022] The suspension may also be a mixture of different suspensions, for example containing zirconia of different colors.

[0023] In the process according to the invention, the zirconia is present as a suspension in a liquid medium, which in particular contains water.

[0024] It is further preferred that the liquid medium has only a small amount of organic components, and therefore the liquid medium contains organic components in an amount of not more than 5% by weight, preferably not more than 3% by weight, more preferably not more than 2% by weight, and particularly preferably not more than 1% by weight, relative to the amount of solids in the suspension.

[0025] In a further preferred embodiment, the liquid medium contains organic components in an amount of 0.05 to 5% by weight, in particular 0.1 to 3% by weight, particularly preferably 0.1 to 2% by weight, and particularly preferably 0.1 to 1% by weight, based on the amount of solids in the suspension.

[0026] In particular, dispersants, binders, agents for adjusting the pH value, stabilizers and / or antifoaming agents come into consideration as organic components.

[0027] Dispersants act to prevent suspended particles from agglomerating to form larger particles, and the amount of dispersant in the liquid medium is in particular 0.01 to 5% by weight, preferably 0.1 to 2% by weight, and particularly preferably 0.1 to 1% by weight, relative to the amount of solids in the suspension.

[0028] Suitable dispersing agents are water-soluble polymers such as polyvinyl alcohol, polyethyleneimine, polyacrylamide, polyethylene oxide, polyethylene glycol, homopolymers and copolymers of (meth)acrylic acid, polyvinylpyrrolidone, biopolymers (e.g., starch, alginate, gelatin), cellulose ethers (e.g., carboxymethylcellulose), vinyl sulfonic acid and vinyl phosphonic acid.

[0029] Preferred dispersants are amino alcohols (such as ethanolamine), glycols (such as ethylene glycol and dipropylene glycol), carboxylic acids (such as maleic acid and citric acid), and carboxylate salts, as well as mixtures of these dispersants.

[0030] It is further preferred that the liquid medium contains at least one compound selected from amino alcohols, glycols, carboxylic acids and carboxylates, and particularly preferred that the liquid medium contains at least one compound selected from ethanolamine, ethylene glycol, dipropylene glycol, citric acid and citrates.

[0031] The binder promotes the cohesion of the particles in the blank present after step (c). The amount of binder in the liquid medium is in particular 0.01 to 5% by weight, more preferably 0.01 to 3% by weight, and particularly preferably 0.01 to 2% by weight, relative to the amount of solids in the suspension.

[0032] Examples of suitable binders are methylcellulose, sodium carboxymethylcellulose, starch, dextrin, sodium alginate, ammonium alginate, polyethylene glycol, polyvinyl butyral, acrylate polymers, polyethyleneimine, polyvinyl alcohol and polyvinylpyrrolidone.

[0033] Preferred binders are polyvinyl alcohol, polyvinyl acetate, polyvinylpyrrolidone, polyacrylic acid, copolymers of acrylic acid esters and acrylic acid, polyethyl acrylate, polymethacrylic acid, polymethyl methacrylate, ammonium polyacrylate, ammonium polymethacrylate, polyethylene glycol, and solid copolymers of ethylene glycol and propylene glycol.

[0034] A further advantage of the blanks obtained by the process according to the invention is that, despite the small amount of binder, they have sufficient strength to be machined (e.g., by grinding and milling) to form the desired dental restoration, even without prior pre-firing.

[0035] Acids and bases (e.g., carboxylic acids (e.g., 2-(2-methoxyethoxy)acetic acid and 2-[2-(2-methoxyethoxy)ethoxy]acetic acid), inorganic acids (e.g., hydrochloric acid and nitric acid), and ammonium hydroxide and tetramethylammonium hydroxide) are particularly contemplated as agents for adjusting the pH value and as stabilizers. Preferably, the liquid medium contains tetramethylammonium hydroxide.

[0036] Antifoaming agents act to prevent the formation of bubbles in the suspension. They are typically used in the liquid medium in an amount of 0.001 to 1% by weight, preferably 0.001 to 0.5% by weight, and particularly preferably 0.001 to 0.1% by weight, based on the amount of solids in the suspension. Examples of suitable antifoaming agents are paraffin, silicone oil, alkylpolysiloxane, higher alcohols, propylene glycol, ethylene oxide-propylene oxide adducts, and, in particular, alkylpolyalkylene glycol ethers.

[0037] It is possible for components of the liquid medium to perform multiple functions, for example both a dispersant and a binder, or both a dispersant and an agent for adjusting the pH value and a stabilizer.

[0038] Since the proportion of organic components is small, these can also be removed from the blank in a short time by burning, a procedure also commonly referred to as debinding.

[0039] It is further preferred that the suspension has a viscosity of 5 mPas to 500 mPas, preferably 5 mPas to 400 mPas, and particularly preferably 5 to 300 mPas. This viscosity is measured using a rotational viscometer (MCR302 Modular Compact Rheometer, manufactured by Anton Paar GmbH) with a cone-plate system with a diameter of 50 mm and an angle of 1°, with a viscosity of 0.1 to 1000 s. -1 The measurements were carried out at a range of shear rates and at a temperature of 25°C.

[0040] To produce the suspension, the zirconia is typically in powder form and thoroughly mixed with the liquid medium. For example, a mixture of zirconia of different colors can also be used here. During this mixing, any agglomerates present are usually also broken down, and grinding of the zirconia used can also be performed to produce the desired particle size. Thus, mixing of the zirconia with the liquid medium can advantageously be carried out, for example, in an agitator bead mill.

[0041] This suspension is then introduced into a mold having pores in step (a) of the process according to the invention. This introduction is usually carried out by pouring. These pores are openings through which the liquid medium can be at least partially removed from the suspension in step (b), so that the zirconia particles can be deposited in the mold and finally form the blank. The geometry of the mold therefore corresponds to the geometry of the desired blank. The mold can therefore already have, for example, a holding device (e.g., a holding pin) formed integrally with the blank, thereby eliminating the need for subsequent attachment (e.g., by gluing).

[0042] In a preferred embodiment of the process according to the invention, the blank formed in step (c) therefore comprises a holding device.

[0043] Typically, substantially all of the liquid medium is removed through the pores. However, it is also possible for residual liquid that is not removed through the pores to be poured or aspirated from the mold. This is usually the case when a sufficiently thick layer of zirconia particles has already been deposited.

[0044] To produce blanks with areas of different color and / or translucency, suspensions of zirconia powder with different compositions can be introduced into the mold one after the other, and for each one a layer of different zirconia particles can be deposited with the desired thickness.

[0045] Thus, in a preferred embodiment of the process according to the invention, in step (a), suspensions of zirconia powders having different compositions, and in particular different colors and / or translucencies, are introduced into the mold one after the other, with measures taken to prevent the suspensions of different compositions from mixing together. This can be achieved, for example, by ensuring that a layer deposited from one suspension is first dried and thus solidified before a further suspension of a different composition is introduced into the mold.

[0046] This mold can be, for example, one of the molds normally used for slip casting or pressure casting processes. These are in particular molds with walls made of gypsum, through which water can be removed from the suspension due to the capillary action of the gypsum pores. However, molds made of plastic, ceramic or metal, which already have pores or which are provided with pores by including filter elements (for example, membrane filters, paper filters and sintered filters), can also be used.

[0047] The mold used is preferably made up of several parts, in order to facilitate the easy removal of the formed blank from the mold. In a particularly preferred embodiment, the mold has connecting parts through which pressure can be applied to the introduced suspension, for example by compressed air, and / or negative pressure can be applied to the pores. Both measures accelerate the removal of the liquid medium from the mold and thus shorten the process. With this aid, a very fast and economical production of zirconia blanks is possible, which is particularly advantageous, especially when producing on an industrial scale.

[0048] The blank formed by the process according to the present invention can have any desired shape. In particular, a shape is selected that allows for easy machining of the blank with conventional dental grinding and milling devices. The blank is preferably provided as a block, a block with an interface (e.g., a hole as an implant interface), a disk, or a tooth-like preform. Preferably, the blank also has a holding device (e.g., a holding pin) integrally formed therewith. This eliminates the need for subsequent attachment of a holding fixture by gluing, as was previously the case. The holding device serves to secure the blank to a machining device (e.g., a CAM machine).

[0049] After removal from the mold in step (c), the formed blank is usually dried. This drying is carried out at temperatures in particular of 20 to 60°C, preferably 20 to 50°C, and particularly preferably 20 to 40°C. The duration of this drying is in particular 0.1 to 24 hours, preferably 0.5 to 12 hours, and particularly preferably 1 to 6 hours. This drying can be carried out, for example, in a climate-controlled cabinet or by microwave drying.

[0050] The blank obtained after completion of step (c) and subsequent optional drying is in the so-called green state and is therefore also called green compact. Surprisingly, in this state, the blank has a very high density, between 3.3 and 4.0 g / cm. 3 , especially 3.35 to 3.9 g / cm 3 , and preferably 3.4 to 3.9 g / cm 3 Preferably, the density is determined by mercury porosimetry in accordance with ISO 15901-1:2016.

[0051] In a more preferred embodiment, the blank in its unfired state has a thickness of 0.08 to 0.14 cm 3 / g, especially 0.08~0.12cm 3 / g, and particularly preferably 0.08 to 0.10 cm 3 / g, which was determined by mercury porosimetry in accordance with ISO 15901-1:2016.

[0052] In another preferred embodiment, the blank in the unfired state has a D relative to the volume of the grains. 50 The pore diameters, measured as a function of the pore diameter, are preferably 0.02 to 0.12 μm, in particular 0.03 to 0.10 μm and particularly preferably 0.04 to 0.08 μm, determined by mercury porosimetry in accordance with ISO 15901-1:2016.

[0053] Already in this green state, the blank can be machined, if necessary after prior removal of organic components, in order to give it the shape of the desired dental restoration.

[0054] The removal of organic components, also called debinding, is carried out in particular by heat treatment at temperatures of about 600° C. A heating rate of 0.125 K / min to 10 K / min, preferably 0.250 K / min to 5 K / min and particularly preferably 0.5 K / min to 2 K / min, is usually selected starting from room temperature up to about 600° C.

[0055] However, it is preferred that the green blank is also pre-fired, which increases the strength and hardness of the blank, in particular at temperatures in the range of 600 to 1100°C, preferably 700 to 1050°C, and particularly preferably 800 to 1000°C, in particular for a duration of 5 minutes to 24 hours, preferably 10 minutes to 12 hours, and particularly preferably 30 minutes to 6 hours.

[0056] Pre-fired blanks have a density of 3.4-4.0 g / cm 3 , especially 3.5 to 4.0 g / cm 3 , and particularly preferably 3.6 to 3.9 g / cm 3 It is preferred that the density of the cellulose acylate is 0.05 to 0.15.

[0057] According to a further preferred embodiment, the pre-fired blank has a thickness of 0.08 to 0.14 cm 3 / g, especially 0.08~0.12cm 3 / g, and preferably 0.09 to 0.11 cm 3 / g, which was determined by mercury porosimetry in accordance with ISO 15901-1:2016.

[0058] In a further preferred embodiment, the pre-fired blank has a maximum pore diameter of less than 0.15 μm, preferably less than 0.12 μm, and particularly preferably less than 0.08 μm, determined by mercury porosimetry in accordance with ISO 15901-1:2016.

[0059] The present invention also relates to a zirconia blank obtainable by the process according to the invention, which has a special structure compared to conventional blanks, since, after the desired shaping, it can be dense-sintered within a very short time to form a dental restoration with very good optical properties (e.g. translucency).

[0060] The present invention is a preformed and 3.4 to 4.0 g / cm 3 , especially 3.5 to 4.0 g / cm 3 , and preferably 3.6 to 3.9 g / cm 3 Density of 0.08-0.14 cm 3 / g, especially 0.08~0.12cm 3 / g, and preferably 0.09 to 0.11 cm 3 / g and / or a maximum pore diameter of less than 0.15 μm, in particular less than 0.12 μm and preferably less than 0.08 μm.

[0061] The blanks according to the invention can be advantageously used to manufacture dental restorations formed therefrom, which, after shaping to form the desired dental restoration, can be dense-fired for only a very short time to form a dental restoration having outstanding optical properties and high strength, thereby making it possible to provide the patient with a dental restoration very quickly.

[0062] The blank according to the invention is further characterized in that it undergoes only slight linear shrinkage during dense firing, which makes the preparation of dental restorations with precisely desired dimensions easier and improves the accuracy of their fit.

[0063] The blanks according to the invention preferably have a linear shrinkage of less than 18%, in particular less than 17% and particularly preferably less than 16%. The linear shrinkage S is given by the following formula and for its determination measurements were carried out in a Netzsch DIL402 Supreme dilatometer in the temperature range from 20°C to 1550°C at a heating rate of 2 K / min on test specimens with dimensions length = 25 mm ± 1 mm, width = 5 mm ± 0.5 mm and height = 4 mm ± 0.5 mm.

number

number

[0064] The present invention therefore also relates to the use of a blank according to the invention for the preparation of a dental restoration, a preferred embodiment of which is explained below in connection with the description of the process according to the invention for the preparation of a dental restoration.

[0065] The process for preparing a dental restoration according to the invention is characterized in that a blank according to the invention is given the shape of the dental restoration and this blank is dense-sintered at a firing temperature of 1200 to 1600°C, in particular 1300 to 1550°C, and preferably 1350 to 1500°C.

[0066] The shaping of this blank is carried out in particular by machining, for example by computer-controlled grinding and milling devices, as is usual in the dental field.

[0067] After formation, a coloring solution may also be applied to the blank, if desired, to achieve the desired color in the final dental restoration.

[0068] Subsequent dense firing produces a molded blank with a density of 5.9 g / cm 3 Higher, preferably 6.00 g / cm 3 Higher, and particularly preferably 6.02 g / cm 3 Formed into dental restorations having higher densities.

[0069] Also with regard to this high density, the resulting dental restorations have outstanding mechanical properties.

[0070] It is particularly advantageous that the entire dense firing process, involving heating from room temperature, holding at the maximum firing temperature, and cooling, takes up only a very short time, and after its completion, a dental restoration is nevertheless obtained that has the required high translucency and very good mechanical properties. The process according to the invention is therefore superior to conventional processes that require a very long time to produce a dental restoration with comparable translucency by firing. The process according to the invention therefore combines the advantages of a very short process duration with the advantages of very good optical and mechanical properties of the dental restorations produced.

[0071] In a preferred embodiment of the process according to the invention, the period during which the shaped blank is heated from room temperature to the firing temperature for dense firing, held at this firing temperature and cooled to the final temperature is 120 minutes or less, in particular 60 minutes or less, preferably 40 minutes or less and particularly preferably 30 minutes or less. "Final temperature" here means a temperature at which the sample can be held in the hand, in particular 15 to 80°C, preferably 25 to 60°C and particularly preferably about 50°C. "Room temperature" means in particular a temperature of 15 to 30°C, preferably 20 to 25°C and particularly preferably about 25°C.

[0072] The heating rate is in particular greater than 50 K / min, preferably greater than 100 K / min, and particularly preferably greater than 200 K / min. The holding time is in particular less than 30 minutes, preferably less than 20 minutes, and particularly preferably less than 10 minutes. The cooling rate from the calcination temperature to the final temperature is in particular greater than 50 K / min, preferably greater than 100 K / min, and particularly preferably greater than 150 K / min.

[0073] The low linear shrinkage that the shaped blanks according to the invention undergo during dense firing makes it easier to prepare dental restorations having precisely the desired dimensions and improves the accuracy of their fit.

[0074] In a preferred embodiment, the blank comprises: (a) subjected to a first heat treatment; (b) subjected to a second heat treatment; and (c) cooled; The heat treatment in step (a) is carried out at a lower pressure than the heat treatment in step (b). In step (a), the blank is preferably heated to a temperature in the range of 1100 to 1600°C, in particular in the range of 1200 to 1500°C, preferably in the range of 1250 to 1450°C, more preferably in the range of 1300 to 1400°C, and most preferably to a temperature of about 1350°C. It is further preferred that the heat treatment in step (a) is carried out at a pressure of less than 200 mbar, preferably less than 100 mbar, and particularly preferably less than 50 mbar, and in particular at a pressure in the range of 0.1 to 200 mbar, preferably 1 to 150 mbar, and particularly preferably 50 to 100 mbar. In step (b), the blank is preferably (b1) further heated if necessary, and (b2) held and fired, preferably at a constant temperature in the range of 1100 to 1700°C, in particular in the range of 1300 to 1600°C, and preferably in the range of 1350 to 1550°C, and particularly preferably at about 1500°C. The heat treatment in step (b) is also preferably carried out at a pressure higher than 500 mbar, and in particular at ambient pressure, and in particular in an oxygen-containing atmosphere (e.g., air, oxygen-enriched air, or oxygen). It is particularly preferred that the oxygen-containing atmosphere, preferably air, oxygen-enriched air, or oxygen, flows discontinuously or preferably continuously through the heating chamber used for heating in step (b), in particular at a flow rate of 0.1 to 50 l / min, preferably 1 to 20 l / min, and particularly preferably 4 to 8 l / min. In a particularly preferred embodiment, in step (a) the blank is heated to a temperature that is 0 to 500 K, in particular 10 to 250 K, preferably 50 to 200 K, and particularly preferably 100 to 150 K lower than the temperature or temperature range at which the blank is held in step (b).

[0075] The dental restoration obtained after compact firing may also be optionally given a veneering surface, polished, and / or polished.

[0076] The dental restorations produced using the process according to the invention are in particular bridges, inlays, onlays, crowns, veneers, implants, occlusal surfaces or abutments.

[0077] The invention is explained in more detail below with reference to examples. [Example]

[0078] Example 1: Suspension containing 76% by weight of zirconia 3.15 g of citric acid or citrate-containing dispersant (Dolapix CE64, manufactured by Zschimmer & Schwarz) and 1.5 g of tetramethylammonium hydroxide were dissolved in 194.4 g of distilled water, in that order, to give a solution with a pH of 10 to 10.5.

[0079] This solution was placed in the storage tank of a MicroCer agitator bead mill (manufactured by Netzsch). The grinding chamber and its rotor were made of zirconia. The grinding chamber was filled with 60 ml of zirconia grinding beads (manufactured by Tosoh) with a diameter of 0.2–0.3 mm. The solution was continuously pumped through the grinding chamber using a peristaltic pump (tubing inner diameter: 8 mm) at a rotor rotation speed of 1500 rpm. 630 g of zirconia powder (TZ-PX-245, manufactured by Tosoh Corporation, primary particle size: 40 nm) partially stabilized with 3 mol% Y2O3 was then added to the solution in the storage tank with continuous stirring. Once the addition of the zirconia powder was complete, the resulting mixture was pumped through the grinding chamber and returned to the storage tank continuously for 45 minutes at a rate of approximately 40 l / h. The suspension prepared in this way was transferred into a plastic measuring beaker and stirred very slowly with a magnetic stirrer to remove trapped air bubbles, and one drop of alkyl polyalkylene glycol ether (Contraspum, Zschimmer & Schwarz) was added as an antifoaming agent.

[0080] The resulting suspension had a zirconia content of 76% by weight. The viscosity η of this suspension was 7.25 mPas (500 s -1 at a shear rate of and a temperature of 25°C).

[0081] (A) Preparation of test specimens Test specimens were prepared, and various properties were determined. For their preparation, the resulting suspension was poured into a disk-shaped mold consisting of a porous gypsum plate fitted with a plastic ring. Water was removed from the suspension by capillary action of the porous gypsum, and a monolithic green body was formed. The green body was left in the mold and allowed to dry in air for 24 hours. After drying was complete, the test specimens were removed from the mold. Each specimen had the following properties: - Linear shrinkage: 15.43% (specimen: length = 25mm ± 1mm, width = 5mm ± 0.5mm and height = 4mm ± 0.5mm) - Density: 3.678g / cm 3 (Test piece: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm)

[0082] (B) Preparation of blocks for "chairside" use A pressure casting mold was used to prepare blocks for "chairside" application. The pressure casting mold consisted of a top part with a connection for compressed air (positive pressure 0.1-100 bar), a middle part corresponding to the desired shape of the block, and a bottom part with a connection for applying vacuum to its base, which contained a membrane filter, a paper filter, and a sintered filter. The membrane filter had a pore size of 200 nm.

[0083] The suspension was poured into the compression mold. Compressed air with a pressure of 6 bar was then supplied through the top part, and a vacuum of about 0.05 bar was applied through the bottom part. After 4 hours, the supply of compressed air and the application of vacuum were terminated. The compression mold was disassembled, and the resulting block was dried in air at 20°C for 24 hours.

[0084] The blocks produced in this way were pre-fired at 950°C for 2 hours. The heating rate was 0.250 K / min. They were then cooled to room temperature within 24 hours. The hardness of these blocks was measured by the Vickers method according to ISO 14705:2008 and EN ISO 6507-1:2005 under a load of 2.5 kg. The hardness was 992.95 N / mm 2 It was.

[0085] Anterior crowns, to which staining liquid was applied with a brush for staining, were dry-milled from pre-fired blocks using a CAD / CAM machine (Zenotec® Select, manufactured by Ivoclar Vivadent AG). After staining, the crowns were dried and then densely fired in a firing oven (Programat CS4, program 1, manufactured by Ivoclar Vivadent AG). This firing took only about 35 minutes. The temperature schedule is shown below. Approximately 25°C to 900°C (6.7 minutes) 900℃ to 1460℃ (11.2 min) 1460°C to 1460°C (5.0 min) 1460℃ to 1200℃ (3.7 min) From 1200℃ to approximately 1000-950℃ (45-50 seconds) (open the furnace) 950℃~1000℃ to about 50℃ (7 minutes)

[0086] Example 2 Suspension containing 83% by weight of zirconia For the preparation of a suspension containing 83 wt. % zirconia and its processing to form test specimens (A) and blocks for "clinical" use (B), Example 1 was repeated with the following changes: the solution contained 164.5 g of distilled water, 4.05 g of citric acid or citrate-containing dispersant (Dolapix CE64, Zschimmer & Schwarz) and 1.5 g of tetramethylammonium hydroxide, and 810 g of zirconia powder partially stabilized with 5 mol. % YO (TZ-PX-430, TOSOH Corporation, primary particle size: 90 nm) was added, and pre-calcination was carried out at 900 °C for 2 h, the heating rate of which was also 0.250 K / min.

[0087] The viscosity η of this suspension was 7.0 mPas (1000 s -1 at a shear rate of and a temperature of 25°C). Representative test specimens obtained according to (A) had the following properties: - Linear shrinkage: 14.43% (specimen: length = 25mm ± 1mm, width = 5mm ± 0.5mm and height = 4mm ± 0.5mm) - Density: 3.791g / cm 3 (Test piece: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm)

[0088] The hardness of the pre-fired blocks obtained according to (B) was measured by the Vickers method in accordance with ISO 14705:2008 and EN ISO 6507-1:2005 under a load of 2.5 kg. The hardness was 496.91 N / mm 2 It was.

[0089] Anterior crowns, to which staining liquid was applied with a brush for staining, were dry-milled from pre-fired blocks using a CAD / CAM machine (Zenotec® Select, manufactured by Ivoclar Vivadent AG). After staining, the crowns were dried and then densely fired in a firing oven (Programat CS4, program 1, manufactured by Ivoclar Vivadent AG). The firing took only 34 minutes. The temperature schedule is shown below. Approximately 25°C to 900°C (6.7 minutes) 900℃ to 1460℃ (11.2 min) 1460°C to 1460°C (5.0 min) 1460℃ to 1200℃ (3.7 min) From 1200℃ to approximately 1000-950℃ (45-50 seconds) (open the furnace) 950℃~1000℃ to about 50℃ (7 minutes)

[0090] Example 3 Suspension containing 80% by weight of zirconia For the preparation of a suspension containing 80 wt % zirconia and its processing to form test specimen (A), Example 1 was repeated with the following changes: the solution contained 179.5 g of distilled water, 3.6 g of a citric acid or citrate-containing dispersant (Dolapix CE64, manufactured by Zschimmer & Schwarz) and 1.5 g of tetramethylammonium hydroxide, and 720 g of zirconia powder partially stabilized with 4.25 mol % YO (TZ-PX-551, manufactured by TOSOH Corporation, primary particle size: 90 nm) was added.

[0091] The viscosity η of this suspension was 14.6 mPas (500 s -1 at a shear rate of and a temperature of 25°C). The test specimens obtained according to (A) had the following properties: - Linear shrinkage: 14.59% - Density: 3.780g / cm 3 .

[0092] The specimens obtained according to (A) were pre-fired at 1000°C for 2 hours. The heating rate was 0.250 K / min. The specimens were then cooled to room temperature within 24 hours. The pre-fired specimens had a linear shrinkage of 13.88%.

[0093] Example 4 Suspension containing 76% by weight of zirconia For the preparation of a suspension containing 76 wt. % zirconia and its processing to form blocks (B) for "chairside" applications, Example 1 was repeated with the following modifications: 630 g of zirconia powder partially stabilized with 3 mol % Y2O3 (AuerDent 3Y-5A A2, Treibacher Industrie AG, primary particle size: 40 nm) was added to the solution, and pre-calcination was carried out at 820°C for 2 h, the heating rate of which was also 0.250 K / min.

[0094] The hardness of the pre-fired blocks obtained according to (B) was measured by the Vickers method in accordance with ISO 14705:2008 and EN ISO 6507-1:2005 under a load of 2.5 kg. The hardness was 440.38 N / mm 2 It was.

[0095] Furthermore, discs were cut from the pre-fired blocks and dense fired in a firing oven (Programat CS4, Ivoclar Vivadent AG) for no more than 34 minutes according to the following temperature schedule: Approximately 25°C to 900°C (6.7 minutes) 900℃ to 1460℃ (11.2 min) 1460°C to 1460°C (5.0 min) 1460℃ to 1200℃ (3.7 min) From 1200℃ to approximately 1000-950℃ (45-50 seconds) (open the furnace) 950℃~1000℃ to about 50℃ (7 minutes)

[0096] The dense fired disc had a brightness ratio CR of 89.16, which was determined using a spectrophotometer (Minolta CM-3700d) in accordance with BS 5612 (British Standard). It is a measure of the opacity of a material, with a brightness ratio of 100 corresponding to a completely opaque material and a brightness ratio of 0 corresponding to a completely translucent material.

[0097] The measured value of 89.16 indicates the high translucency of the sample produced according to the invention, which in the case of conventionally produced blanks could only be achieved using very long baking times, greater than 2 hours.

[0098] Example 5 Suspension containing 83% by weight of zirconia For the preparation of a suspension containing 83 wt. % zirconia and its processing to form test specimen (A), Example 1 was repeated with the following changes: the solution contained 164.5 g of distilled water, 3.15 g of a citric acid or citrate-containing dispersant (Dolapix CE64, manufactured by Zschimmer & Schwarz) and 1.5 g of tetramethylammonium hydroxide, and 810 g of zirconia powder partially stabilized with 3 mol. % YO (TZ-PX-245, manufactured by TOSOH Corporation, primary particle size: 40 nm) was added. The test specimens obtained according to (A) were debonded at 500°C and had the following properties: - Pore volume: 0.11391cm 3 / g - Pore radius: 0.0190μm - Density: 3.5617g / cm 3 (Test piece: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm)

[0099] The debonded specimens were then pre-fired for 2 hours at 1050° C. The pre-fired blanks thus obtained had the following properties: - Pore volume: 0.09931cm 3 / g - Pore radius: 0.0242μm - Density: 3.8866g / cm 3 (Test piece: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm)

[0100] The debonded specimens were similarly pre-fired for 2 hours at 1000° C. The resulting pre-fired blanks were dense fired in a firing furnace (Cerec Speedfire, manufactured by Dentsply Sirona) for no more than 20 minutes according to the following temperature schedule: Approximately 25°C to 500°C (88 seconds) 500℃ to 1580℃ (190 seconds) 1580℃ to 1580℃ (360 seconds) 1580℃ to 950℃ (120 seconds) 950℃ to approx. 50℃ (420 seconds)

[0101] Example 6 Suspension containing 83 wt% zirconia + vacuum For the preparation of a suspension containing 83 wt % zirconia and its processing to form test specimen (A), Example 1 was repeated with the following changes: the solution contained 164.5 g of distilled water, 4.05 g of a citric acid or citrate-containing dispersant (Dolapix CE64, manufactured by Zschimmer & Schwarz) and 1.5 g of tetramethylammonium hydroxide, and 810 g of zirconia powder partially stabilized with 3 mol % YO (TZ-PX-245, manufactured by TOSOH Corporation, primary particle size: 40 nm) was added.

[0102] The specimens obtained according to (A) were debonded and pre-fired, in which they were heated at a rate of 0.25 K / min to a temperature of 1000° C. and kept at this temperature for 2 hours.

[0103] The resulting pre-fired blanks were densely fired in a firing furnace equipped with MoSi heating elements for a maximum of only 36 minutes according to the following temperature schedule: the first two steps were carried out under reduced pressure in the range of 50-100 mbar, and after air supply, the further steps were carried out under ambient atmosphere with continuous air flushing. Approximately 25°C to 950°C (7.1 min) under reduced pressure 950℃ to 1450℃ (10 min) under reduced pressure 1450°C to 1500°C (1 min) in continuous air flow in ambient atmosphere 1500°C to 1500°C (5 min) in ambient atmosphere with continuous flow of air 1500℃ to 1100℃ (2.9 min) ambient atmosphere From 1100℃ to approximately 50℃ (5-10 minutes) Ambient atmosphere

[0104] To investigate the optical properties, these dense sintered specimens were ground parallel to the face (20 μm diamond disc) to a thickness of 2 mm ± 0.02 mm and a diameter of 18 mm ± 0.5 mm, and then polished (SiC paper, grit 1000).

[0105] The dense-fired discs had a brightness ratio, CR, of only 78.95%. These discs therefore demonstrated very high translucency and the favorable effect of the use of reduced pressure during dense firing and subsequent atmosphere exchange.

[0106] Example 7 Suspension containing 83% by weight of zirconia For the preparation of a suspension containing 83 wt % zirconia and its processing to form test specimen (A), Example 1 was repeated with the following changes: the solution contained 164.5 g of distilled water, 3.15 g of a citric acid or citrate-containing dispersant (Dolapix CE64, manufactured by Zschimmer & Schwarz) and 2.0 g of tetramethylammonium hydroxide, and 810 g of zirconia powder partially stabilized with 4.25 mol % YO (TZ-PX-551, manufactured by TOSOH Corporation, primary particle size: 90 nm) was added. The test specimens obtained according to (A) were debonded at 500°C and had the following properties: - Pore volume: 0.11087cm 3 / g - Pore radius: 0.0248μm - Density: 3.5474g / cm 3 (Test piece: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm)

[0107] The debonded specimens were then pre-fired for 2 hours at 1050° C. The pre-fired blanks thus obtained had the following properties: - Pore volume: 0.10282cm 3 / g - Pore radius: 0.0315μm - Density: 3.6838g / cm 3 (Test piece: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm)

[0108] Example 8 Suspension containing 83% by weight of zirconia For the preparation of a suspension containing 83 wt % zirconia and its processing to form test specimen (A), Example 1 was repeated with the following changes: the solution contained 164.5 g of distilled water, 3.15 g of a citric acid or citrate-containing dispersant (Dolapix CE64, manufactured by Zschimmer & Schwarz) and 2.0 g of tetramethylammonium hydroxide, and 810 g of zirconia powder partially stabilized with 5.0 mol % YO (TZ-PX-430, manufactured by TOSOH Corporation, primary particle size: 90 nm) was added. The test specimens obtained according to (A) were debonded at 500°C and had the following properties: - Pore volume: 0.10559cm 3 / g - Pore radius: 0.0253μm - Density: 3.7831g / cm 3 (Test piece: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm)

[0109] The debonded specimens were then pre-fired for 2 hours at 1050° C. The pre-fired blanks thus obtained had the following properties: - Pore volume: 0.10311cm 3 / g - Average pore radius: 0.0318μm - Density: 3.9083g / cm 3 (Specimen: length = 5mm ± 1mm, width = 5mm ± 1mm ​​and height = 10mm ± 1mm).

Claims

1. A process for the preparation of a zirconia blank for the preparation of a dental restoration, comprising the steps of: (a) a suspension of zirconia in a liquid medium is introduced into a mold having a porous structure; (b) the liquid medium is at least partially removed through the pores; and (c) the formed blank is removed from the mold; the suspension having a zirconia content of 68 to 88 wt. %; the liquid medium comprises water; the liquid medium contains an organic component in an amount of 5% by weight or less based on the amount of solids in the suspension; the organic component comprises a dispersant; The blank has a thickness of 3.3 to 4.0 g / cm 3 and / or a density of 0.08 to 0.14 cm 3 / g pore volume and / or D relative to the volume of the particle 50 The process has a pore diameter measured as a value between 0.02 and 0.12 μm.

2. The zirconia in the suspension has a particle volume of d 50 2. The process of claim 1, having a particle size, measured as a metric value, of 50 to 250 nm.

3. The process of claim 1 or 2, wherein the zirconia in the suspension has a primary particle size of 30 to 100 nm.

4. The zirconia is 2 O 3 , La 2 O 3 , CeO 2 4. The process according to claim 1, wherein the SiO 2 is stabilized with MgO and / or CaO.

5. 5. The process of claim 1, wherein the liquid medium contains organic components in an amount of up to 3% by weight relative to the amount of solids in the suspension, or in an amount of 0.05 to 5% by weight relative to the amount of solids in the suspension.

6. The process of any one of claims 1 to 5, wherein the liquid medium contains at least one compound selected from amino alcohols, glycols, carboxylic acids and carboxylates.

7. The suspension is heated for 0.1 to 1000 s -1 7. The process according to claim 1, wherein the viscosity of the emulsion is from 5 to 500 mPas, measured at a shear rate of 100 rpm and at a temperature of 25°C.

8. The process of any one of claims 1 to 7, wherein the suspension contains a mixture of zirconia powders having different compositions.

9. A process according to any one of claims 1 to 8, wherein in step (a) suspensions of zirconia powders having different compositions are introduced into the mould one by one in sequence.

10. The process according to any one of claims 1 to 9, wherein the blank is a block, a block with an interface, a disc or a tooth-like preform.

11. The process of any one of claims 1 to 10, wherein the blank formed in step (c) has a holding device.

12. The process of any one of claims 1 to 11, wherein the blank formed in step (c) is dried.

13. The blank has a density of 3.35 to 3.9 g / cm3; and / or 0.08~0.12cm 3 / g pore volume, and / or D relative to the volume of the particle 50 The process of any one of claims 1 to 12, having a pore diameter, measured as a value, of 0.03 to 0.10 μm.

14. The process according to any one of claims 1 to 13, wherein the blank is pre-fired.

15. The pre-fired blank is A density of 3.4 to 4.0 g / cm3, and / or 0.08~0.14cm 3 / g pore volume, and / or Maximum pore diameter less than 0.15 μm 15. The process of claim 14, comprising:

16. A zirconia blank for the preparation of a dental restoration, obtainable by the process according to any one of claims 1 to 15.

17. 17. The zirconia blank of claim 16 having a linear shrinkage of less than 18%.

18. Use of a blank according to claim 16 or 17 for the preparation of a dental restoration.

19. 18. A process for the preparation of a dental restoration, in which a blank according to claim 16 or 17 is given the shape of a dental restoration and the blank is dense fired at a firing temperature of 1200 to 1600°C.

20. 20. The process of claim 19, wherein the period of time for heating the blank from room temperature to the firing temperature, holding at the firing temperature, and cooling to the final temperature is 120 minutes or less.

21. The blank is (a) subjected to a first heat treatment; (b) subjected to a second heat treatment; and (c) being cooled; 21. The process of claim 19 or 20, wherein the heat treatment in step (a) is carried out at a lower pressure than the heat treatment in step (b).

22. The process according to any one of claims 19 to 21, wherein the dental restoration is a bridge, an inlay, an onlay, a crown, an implant, a veneer, an occlusal surface or an abutment.

Citation Information

Patent Citations

  • Fabrication method for ceramic core of a dental prosthesis

    EP0826642A2

  • Treatment of casting mold for dental purpose and mold coating material

    JP1994142119A

  • Injection ceramic mesh-form structure to manufacture tooth die and dental filler

    JP1997098990A

  • Doped zirconia ceramic

    JP2012509837A

  • Zirconia composition, zirconia calcinated body, zirconia sintered body and manufacturing zirconia sintered body and dental product

    JP2016117618A